PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS X-IPA2 MAN 1 JEMBRANA PADA MATERI ELEKTROLIT MELALUI MODEL PROJECT BASED LEARNING SECARA BLENDED LEARNING - HENDAH TRI SULYANTARI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2023)
Learning Electrolyte Solutions for class X even semester of the 2020-2021 academic year emphasizes conceptual and abstract nature so that students do not understand it. During the Covid-19 pandemic and New Normal it was not easy to use learning methods like face-to-face learning. The method that is often used online is giving assignments. Preliminary test results obtained the lowest score 28 and the highest 85, learning completeness 16%. The low value of learning completeness causes the writer to want to change the learning method so that learning mastery is achieved. The method chosen by project based learning is blended learning. Learning outcomes increased learning outcomes from cycle 1 to 2, ranging from 12% in terms of absorption. Improved skills assessment 14%. Online learning with YouTube has improved learning outcomes, but attitudes, skills and affective assessments are less visible. Offline learning with practicum further improves learning outcomes, assessment of attitudes, skills and affective is clearly visible. ABSTRAKPembelajaran Larutan Elektrolit kelas X semester genap tahun pelajaran 2020-2021 menekankan konseptual dan bersifat abstrak sehingga kurang dipahami siswa. Dimasa pandemi Covid-19 dan New Normal tidak mudah menggunakan metode pembelajaran seperti pada pembelajaran tatap muka. Metode yang sering digunakan saat daring adalah pemberian tugas. Hasil tes awal didapat nilai terendah 28 dan tertinggi 85, ketuntasan belajar 16 %. Rendahnya nilai ketuntasan belajar menyebabkan penulis ingin merubah metode belajar sehingga ketuntasan belajar tercapai. Metode yang dipilih project based learning secara blended learning. Hasil pembelajaran terjadi peningkatan hasil belajar dari siklus 1 ke 2 berkisar 12 % dilihat dari daya serap. Peningkatan penilaian ketrampilan 14 %. Pembelajaran daring dengan youtube sudah meningkatkan hasil belajar tapi penilaian sikap, ketrampilan dan afektif kurang terlihat. Pembelajaran luring dengan praktikum lebih meningkatkan hasil belajar, penilaian sikap, ketrampilan dan afektif terlihat dengan jelas..